Genetic diversity for sustainable development of animal industry - Panandam, Jothi Malar (2013)
Farm animal genetic resources are not only a source of food and animal protein, but also play a multi-functional role providing other commodities and services. As a result of evolution and environment factors over thousands of years we now have a vast array of species and breeds across the world. The genetic diversity among breeds and populations has been enhanced by the differences in the selection practices among countries and communities. Over the recent decades, however, this genetic diversity has become threatened. Indigenous and local breeds, which are often more adapted to the local environmental conditions and management systems, less prone to local diseases, require low maintenance and have unique qualities, are being replaced by a few high yielding specialised breeds or have their gene pool introgressed with genes from these breeds. The exotic breeds, which have been subjected to high intensity selective breeding, tend to have narrowed genetic base. Furthermore, in many developing countries the genetic diversity within the existing breeds is fast eroding as a result of mismanagement of breeding activities and failure to keep proper records. Genetic diversity is crucial for animals to adapt to changing environmental conditions and to survive in the face of disease outbreaks. It is also the resource for animal breeders to improve livestock productivity to meet current and future demands. The loss of genetic diversity among farm animals should be the concern of all as it affects food security, trade and livelihood of farmers. The stakeholders in the animal industry should realise that the sustainable development and increased productivity of the industry requires the conservation of genetic diversity and the sustainable utilisation and development of farm animal genetic resources.